COVID 19 HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT DENGAN PEMBERIAN VAKSIN COVID 19 DI KELURAHAN TERJUN KECAMATAN MEDAN MARELAN : HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT DENGAN PEMBERIAN VAKSIN COVID 19 DI KELURAHAN TERJUN KECAMATAN MEDAN MARELAN - Martina, Siska Evi; Gultom, Rumondang; Sinaga, Janno; Anugrah, Teguh (Ruang Ide Publisher, 2023)
Abstract Knowledge of COVID-19 patients can be interpreted as the result of knowing from patients about the disease, understanding of the disease, ways of prevention, treatment and complications, Community attitudes to slow transmission, especially among high-risk populations Attitudes are measured according to awareness of social distancing at work and worship , as well as learning from home, Vaccines are substances or substances that function to help the body fight certain diseases. A vaccinated body will form antibodies against certain viruses. Vaccination against Covid-19 is one of the Indonesian government's efforts to deal with the COVID-19 problem. The purpose of this study was to determine the relationship between knowledge and attitudes of the community with the administration of the COVID-19 vaccine in the Waterfall Village, Medan Marelan District. This type of research is a type of quantitative research. The population in this study is the 100 people in the sub-district community. The sample in this study were 80 people from the community. There are 2 sampling techniques, namely probability sampling and accidental sampling. The tool used to conduct the research was a questionnaire sheet, the data were analyzed using the chi-square test. The results showed that there was no relationship between knowledge and giving the COVID-19 vaccine (P=0.150), there was a relationship between people's attitudes and giving the COVID-19 vaccine (P=0.000). Suggestions from this study It is hoped that the public can take part in the COVID-19 vaccination to be able to form body protection from exposure to the virus during the Covid-19 pandemic by continuing to implement a healthy and clean lifestyle and continue to carry out health protocols, so that they can avoid exposure to the COVID-19 virus.